ExplanationLet N = Norman’s age now; (N + 6) = Norman’s age in 6 years.

Let M = Michael’s age now; (M + 6) = Michael’s age in 6 years.

Translate the first two sentences into equations. Note that the second equation deals with Norman and Michael’s ages in 6 years:

\(N = M + 12\)

\((N + 6) = 2(M + 6)\)

The question asks for M, so substitute (M + 12) for N in the second equation:

\((M + 12) + 6 = 2(M + 6)\)

\(M + 18 = 2M + 12\)

\(M + 6 = 2M\)

\(6 = M\)

Hence option B is correct!
_________________

Sandy

If you found this post useful, please let me know by pressing the Kudos Button

Try our free Online GRE Test